Beast from haunted cave - Corman, Gene, 1927-; Hellman, Monte, 1932-; Griffith, Charles B.; Forest, Michael, 1929-; Gene Corman Productions; Cinetel Films ([Los Angeles, CA] : Gene Corman Productions, 1959)
A gang of thieves set off an explosion in an old mine in order to distract the local authorities from their true objective, robbing gold out of the vault of the bank. The gang makes their way to a remote ski lodge, to wait out a storm before crossing the border into Canada, and end up taking some hostages to insure their getaway. Unfortunately for everyone staying at the lodge, their arrival has disturbed a horrible creature residing in a nearby cave, which sets out to satisfy its hunger by stalking the thieves and their hostages.
Originally released as a motion picture in 1959.
Michael Forest, Sheila Carol, Frank Wolff, Wally Campo.
Director of photography, Andrew Costikyan; editor, Anthony Carras; music, Alexander Laszlo.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Thieves -- Drama; Monsters -- Drama; Horror films; Science fiction films; Feature films; Internet videos; Streaming video